States of mutation. Re-configurations of modern state, business, and media - Laura L. Ortiz-Negrón (Pontifícia Universidade Católica do Rio Grande do Sul, 2009)
This article sets out an analysis of the transformations and new configurations between the state, business and media in Puerto Rico. The traditional demarcations between these three spheres are in flux as are their corresponding socio-political networks revealing new public and private scenarios. The state has managed downsizing via "partnership" initiatives with private enterprise and non-governmental organizations. Simultaneously, business has assumed a discourse of "social responsibility" participating in joint projects with the local state agencies and NGOs. The media's increasing involvement in social issues, in at times near independence of state generated directives, and at others, in direct concert with the state, is an important aspect of mediatic society. It shall be argued that the ever-increasing metamorphosis of mass media in tandem with other businesses, now constitute entities assuming roles previously filled exclusively by the state, and a concomitant transformation of the state resulting in the appearance a more mediatic-governmental entity. The new realignment of these spheres underline structural networks that reconfigure the world of the social and the public. In this sense we can identify contemporary social change, requiring re-conceptualization and analysis, as resulting from an emerging social configuration with fluid sociopolitical and cultural forms.